A-18 リン酸オクタカルシウム/ゼラチン複合体の家兎脛骨骨欠損埋入における骨伝導能の評価(セラミックス,一般講演(口頭発表),第66回日本歯科理工学会学術講演会) - 齋藤 慶介; 穴田 貴久; 土屋 香織; 千葉 晋平; 井樋 栄二; 鈴木 治 (日本歯科理工学会誌, 2015)
The present study was designed to investigate whether osteoconductivity of octacalcium phosphate/gelatin (OCP/Gel) composites can be improved by controlling the content of OCP in the composites. The composites with some mixing ratios of OCP were prepared by mixing granules of OCP with Gel. OCP/Gel composites were implanted into the defect in rabbit tibia for 4 or 6 weeks and then examined radiographically, histologically, and histomorphometrically. The results indicated that the content of the OCP granules can control the osteoconductivity of OCP/Gel in the defect of rabit tibia.